Differential MicroRNAs Expression in Prostate Cancer - Delella, Flávia Karina (2012)
Introduction: MicroRNAs are small non-coding RNAs that act as post-transcriptional regulators of mRNA targets. Recent studies suggest that differential expression of some microRNA s are associated with cancer development, invasion and metastasis, including prostate cancer. Improvements in detection techniques and findings of new molecular markers are important tools for early diagnosis and treatment of individual patients. Objective: To carry out a scientific review about the main microRNAs altered in prostate cancer. Methods: The PubMed database was chosen for the research using the key words microRNA and prostate cancer. The discovery and study of microRNAs involved in cancer progression are recent scientific topics and, within the 260 publications found, 25 were selected for this review. Results: Many microRNAs are classified as promoters of cell survival and tumor growth. The papers selected for this review describe differential expression of microRNAs in samples of prostate tumors and prostatic tumor cells studied in vitro. Alterations of microRNAs in plasma, urine and tumor tissue were found to be interesting tools to distinguish patients with prostate cancer from healthy individuals, classifying these molecules as promising biomarkers. Conclusion: The excellent quality of publications highlights the importance of post-transcriptional regulation exerted by microRNAs in prostate cancer progression. Despite being a recent topic, modern molecular techniques are being employed to unveil novel microRNAs and to characterize their mechanisms of action.